Advancement of adsorption process on activated carbon using microwave and high gravimetric technologies / Anirban Kundu - Anirban, Kundu (2016)

(untitled)
This thesis describes the efficacy of microwave technology for the preparation of a novel activated carbon from an agricultural waste and the utilisation of the activated carbon in an innovative rotating packed bed (RPB) contactor. In RPB, centrifugal force provides the driving force for the adsorption of heavy metals and dye such as chromium and Direct Red 23 (DR23) on activated carbon. Activated carbon became a material of choice as an adsorbent for industrial and environmental applications more recently. Typical process of producing activated carbon requires heating a carbonaceous material for one to seven hours. Although activated carbon with surface area ranging between 800 to 1600 m2/g can be produced, the process is slow and inefficient due to heat as well as material losses. Moreover, the contactor volume is often large to meet the process requirement. Consequently, this research is primarily focused on the following objectives: i) optimisation of process variables in microwave assisted activated carbon production from waste material, ii) evaluation of the prepared activated carbon for heavy metal and dye removal, iii) application of high gravimetric (HIGEE) technology in RPB contactor to minimise the contact time for adsorption, and iv) optimisation of the process parameters of RPB contactor for heavy metal and dye removal, estimation of the adsorption kinetics and adsorption isotherm. Activated carbon was prepared using waste palm kernel shells (PKS) as the raw material by two different impregnating materials, namely phosphoric (H3PO4) and sulphuric acid (H2SO4). The activated carbon prepared by microwave activation and based on three different impregnation ratios of H3PO4 had specific surface areas of 872, 1256 and 952 m2 /g. The chromium removal capacity of the activated carbon was 19.1 mg/g. The process parameters for activated carbon preparation were optimised with the aid of Taguchi method and response surface methodology (RSM). The specific surface iv area of the activated carbon, prepared from H3PO4 impregnation and optimised by Taguchi method (denoted as MWACT) was 1473.5 m2/g during initial optimisation, and increased to 1535 m2/g when the operating conditions were fine-tuned. For activated carbon (denoted as MWAC) prepared by H2SO4 impregnation and optimised by RSM, the specific surface area was 1011 m2/g and zinc removal capacity of 14.6 mg/g. The MWACT was applied to remove DR23 and almost total removal was achieved with the removal capacity of 24.75 mg/g. The adsorption in the RPB contactor was much faster than that in a shake flask for the same adsorbent to adsorbate ratio. The removal of DR23 using commercially activated carbon was almost 90% within 5h in RPB contactor in comparison to 55% in a shake flask. In RPB contactor almost 75% of chromium was adsorbed by MWACT within 20 min and 90% within 3 h. Optimum conditions for the adsorption were found to be rotating speed of 1200 rpm, feed rate of 50 L/min, packing density of 179 kg/m3 and initial solution pH of 2. These optimum conditions were robust to the external noise factor, which was initial chromium concentration in solution.